IMPROVING DIAGNOSIS MODEL OF AIRCRAFT ENGINE USING "K-MEANS" - I. J. Buraimah (Научный вестник МГТУ ГА, 2016)
This article deals with, results which are shown using K-Means as a tool for diagnosis of Aircraft engine condition.